Problematika Jadwal Waktu Salat Subuh di Indonesia - Abdul Mughits (Faculty of Sharia and Law - Sunan Kalijaga State Islamic University, 2014)
Lately, the dawn prayer time schedule thats the mainstream in Indonesia